2013
DOI: 10.1093/bja/aet389
|View full text |Cite
|
Sign up to set email alerts
|

Awake insertion of the air-Q™ intubating laryngeal airway device that facilitates safer tracheal intubation in morbidly obese patients

Abstract: Awake insertion of the air-Q TM intubating laryngeal airway device that facilitates safer tracheal intubation in morbidly obese patients Editor-Morbidly obese patients are at a higher risk of difficulties with mask ventilation and tracheal intubation. 1 The difficult airway management algorithm recommends awake intubation in patients anticipated to have difficult airways. Recently, supraglottic airway devices have been established as important tools for difficult airway management. 2 We present an observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A combined approach to ATI using both VL and FB has been described and could be considered in complex clinical scenarios (Grade D). In a well‐topicalised patient, insertion of an SAD as a conduit for ATI:FB has also been described , and may provide the benefit of maintaining airway patency. Single‐use flexible bronchoscopes are associated with a similar safety profile to re‐usable ones .…”
Section: Procedural Setupmentioning
confidence: 99%
“…A combined approach to ATI using both VL and FB has been described and could be considered in complex clinical scenarios (Grade D). In a well‐topicalised patient, insertion of an SAD as a conduit for ATI:FB has also been described , and may provide the benefit of maintaining airway patency. Single‐use flexible bronchoscopes are associated with a similar safety profile to re‐usable ones .…”
Section: Procedural Setupmentioning
confidence: 99%
“…Arslan et al has reported that supraglottic airway device was inserted after the induction of general anesthesia with 1 μg/kg fentanyl, 3 mg/kg propofol and 0.6 mg/kg rocuronium, and then facilitate tracheal intubation in morbidly obese patients [ 12 ]. Shiraishi reported an observational study to show a safer method of airway management in obese patients by performing awake insertion (intravenous injection of 20-40 μg/kg midazolam and 1-2 μg/kg fentanyl) of the supraglottic airway device allowing spontaneous ventilation to facilitate subsequent tracheal intubation [ 13 ]. However, the optimum anesthetics for supraglottic airway device insertion with spontaneous breathing in obese patients have not been standardized.…”
Section: Introductionmentioning
confidence: 99%
“…Isono admonishes that: “Awake intubation should be considered when any element of the triple airway maneuver, including mandible advancement, neck extension and mouth opening, is disturbed in obese patients with severe OSA [31]. ” Though they lack protection against aspiration of gastric contents, supraglottic airway devices — including the laryngeal mask airway (LMA) — can also be used as a rescue technique for ventilation and intubation [32,33]. No specific device can restore oxygenation, but sound planning, clear communication and skillful use of available resources can facilitate navigation through a difficult airway scenario.…”
Section: Oxygenation Before Intubation: Airway Management In the Obesementioning
confidence: 99%